Executive Functions in Aging: An Experimental and Computational Study of the Wisconsin Card Sorting and Brixton Spatial Anticipation Tests. - Caso, Andrea; Cooper, R. P. (Experimental Aging Research)
In order to explore the effect of normal aging on executive function, we tested 25 younger adults and 25 neurologically healthy older adults on the Wisconsin Card Sorting Test (WCST) and the Brixton Spatial Anticipation Test (BRXT), two classic tests of executive function. We found that older participants were more likely than younger participants to err on both tasks, but the additional errors of older participants tended to be related to task set maintenance and rule inference rather than perseveration. We further found that the tendency to perseverate (across all participants) on the WCST was related to the tendency to produce stimulus or response perseverations on the BRXT, rather than any tendency to perseverate on BRXT rule application. Finally, on both tasks, older participants were also slower, particularly on trials following an error, than younger participants. To explore the neurocomputational basis for the observed behaviours we then extended an existing model of schema-modulated action selection on the WCST to the BRXT. We argue on the basis of the model that the performance of older participants on both tasks reflects a slower update of schema thresholds within the basal ganglia, coupled with a decrease in sensitivity to feedback.